Plan de marketing digital para la empresa Pizzería Mozzarelli, Otavalo, Imbabura, Ecuador - Quishpe Quishpe, Carlos Armando (2024)
This research aimed to design a digital marketing plan for the company Pizzería Mozzarelli, located in the city of Otavalo, Imbabura, Ecuador. A mixed methodology was employed, combining qualitative and quantitative approaches. In the qualitative stage, semi structured interviews were conducted with key personnel of the pizzeria to understand its internal operations and opportunities for improvement. Subsequently, an online survey was administered to 380 current and potential customers, collecting quantitative data on preferences, behaviors, and satisfaction. The analysis of the results revealed a significant positive correlation between customer satisfaction and social media interaction (0.890), as well as a willingness to receive offers and promotions through electronic means (0.936). However, areas of opportunity were identified, such as the need to strengthen the digital presence, optimize online customer service, and leverage the strategic location of the physical establishment. Consequently, a digital marketing plan was proposed, addressing these key areas with strategies such as increasing social media activity, training staff in digital customer service, improving the website, expanding home delivery capacity, and implementing innovations in products and services. The main conclusions highlight the importance of digital presence, personalized customer service, constant innovation, and leveraging competitive advantages for the company's sustainable growth.